(untitled) (Communications in Mathematical Research, 2022)
In this paper, we extend the notion of the T-Schur decomposition to the weighted T-core-EP decomposition. Next, the weighted T-core-EP inverse of rectangular tensors is defined by a system, and its existence and uniqueness are obtained. Furthermore, the perturbation of the weighted T-core-EP inverse is studied under several conditions, and the relevant examples are provided to verify the perturbation bounds of the weighted T-core-EP inverse of tensors.